2017
DOI: 10.1038/s41556-017-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

A PERK–miR-211 axis suppresses circadian regulators and protein synthesis to promote cancer cell survival

Abstract: Summary The Unfolded Protein Response (UPR), is a stress activated signaling pathway that regulates cell proliferation, metabolism and survival. The circadian clock coordinates metabolism and signal transduction with light/dark cycles. We have explored how UPR signaling interfaces with the circadian clock. UPR activation induces a 10h phase shift in circadian oscillations through induction of miR-211; miR-211, a PERK inducible micro-RNA, transiently suppresses both Bmal1 and Clock, core circadian regulators. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 43 publications
4
77
0
Order By: Relevance
“…61 Different studies have shown that the UPR is regulated by the circadian clock. 62,63 In Burkitt's lymphoma, repression of BMAL1 is essential for the UPR-dependent inhibition of protein synthesis, 35 and it has been reported that low PER1 expression and high UPR response associate with poorer prognoses in glioblastoma patients. 64 In the current study, melatonin was able to downregulate the overexpressed chaperones HSP70, HSP90, and GRP78 from 20 weeks of DEN administration, and BMAL1 and CLOCK, the central regulator of the circadian clock, decreased from 10 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…61 Different studies have shown that the UPR is regulated by the circadian clock. 62,63 In Burkitt's lymphoma, repression of BMAL1 is essential for the UPR-dependent inhibition of protein synthesis, 35 and it has been reported that low PER1 expression and high UPR response associate with poorer prognoses in glioblastoma patients. 64 In the current study, melatonin was able to downregulate the overexpressed chaperones HSP70, HSP90, and GRP78 from 20 weeks of DEN administration, and BMAL1 and CLOCK, the central regulator of the circadian clock, decreased from 10 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In a genome-wide siRNA screen to identify modulators of circadian rhythm, ATF6 siRNA was identified to shorten the circadian period in U2OS cells 31 and is also another potential input point. Here, we did not observe a shortening of period as a result of ER stress induced ATF6 expression; however this is in-line with a recent study which demonstrated a 10 hour shift in circadian rhythm in cancer cells undergoing ER stress 14 . We have shown that ER stress or misfolded proteins can dramatically suppress clock activation in normal fibroblasts, and this poses the question that cancer cells may negate this suppressive role of the UPR on the clock in order to survive.…”
Section: Discussionsupporting
confidence: 92%
“…We further verified that ZNF205‐AS1 increased EGR4 mRNA stability, and therefore up‐regulated EGR4 expression. microRNAs (miRNAs) are well‐known to bind the 3’UTR of target mRNAs and induce the degradation and/or translation inhibition of target mRNAs . The interaction between ZNF205‐AS1 transcript and EGR4 mRNA 3’UTR may protect EGR4 mRNA from miRNAs‐induced degradation, which need further investigation.…”
Section: Discussionmentioning
confidence: 99%